Prokaryotic Diversity and Community Patterns in Antarctic Continental Shelf Sponges - Steinert, Georg; Wemheuer, Bernd; Janussen, Dorte; Erpenbeck, Dirk; Daniel, Rolf; Simon, Meinhard; Brinkhoff, Thorsten; Schupp, Peter J. (Frontiers in Marine Science, 2019)
Marine sponges (Phylum Porifera) are globally distributed within marine and freshwater ecosystems. In addition, sponges host dense and diverse prokaryotic communities, which are potential sources of novel bioactive metabolites and other complex compounds. Those sponge-derived natural products can span a broad spectrum of bioactivities, from antibacterial and antifungal to antitumor and antiviral compounds. However, most analyses concerning sponge-associated prokaryotes have mainly focused on conveniently accessible relatively shallow sampling locations for sponges. Hence, knowledge of community composition, host-relatedness and biotechnological potential of prokaryotic associations in temperate and cold-water sponges from greater depths (mesophotic to mesopelagic zones) is still scarce. Therefore, we analyzed the prokaryotic community diversity of four phylogenetically divergent sponge taxa from mesophotic to mesopelagic depths of Antarctic shelf at different depths and locations in the region of the South Shetland Islands using 16S rRNA gene amplicon-based sequencing. In addition, we predicted functional profiles applying Tax4Fun from metagenomic 16S rRNA gene data to estimate their biotechnological capability and possible roles as sources of novel bioactive compounds. We found indications that cold and deep-water sponges exhibit host-specific prokaryotic communities, despite different sampling sites and depths. Functional prediction analysis suggests that the associated prokaryotes may enhance the roles of sponges in biodegradation processes of xenobiotics and their involvement in the biosynthesis of secondary metabolites.